Effect of different doses of inhaled ciclesonide on lung function, clinical signs related to airflow limitation and serum cortisol levels in horses with experimentally induced mild to severe airway obstruction. (5th April 2019) - Lavoie, J.‐P.; Bullone, M.; Rodrigues, N.; Germim, P.; Albrecht, B.; von Salis‐Soglio, M.
Summary: Background: Inhaled corticosteroids are effective for the treatment of equine asthma but they induce cortisol suppression with potential side effects. Objectives: To study the efficacy of ciclesonide, an inhaled corticosteroid with an improved safety profile, on lung function, clinical signs related to airway obstruction, and serum cortisol levels in asthmatic horses exposed to a mouldy hay challenge. Study design: Cross‐over placebo controlled, blinded, randomised experiment. Methods: Sixteen horses were enrolled in three subsequent dose‐titration studies (8 horses/study) to investigate the effects of inhaled ciclesonide administered for 2 weeks at doses ranging from 450 to 2700 μg twice daily or 3712.5 μg once daily. Systemic dexamethasone (0.066 mg/kg per os) was our positive control. A placebo group was also studied. Lung function and clinical scores were blindly performed before and after 7 and 14 days of treatment. Serum cortisol was measured before and after 3, 5, 7, 10, 14 days of treatment as well as 3 and 7 days post treatment. Results: After 7 days, dexamethasone induced a significant reduction in pulmonary resistance (from 2.5 ± 0.6 at day 0 to 1.1 ± 0.7 cm H2 O/L/s), pulmonary elastance (5.0 ± 2.6 to 1.2 ± 1.0 cm H2 O/L), and of the weighted clinical score (14.8 ± 4.7 to 8.0 ± 4.4). Similarly, ciclesonide 1687.5 μg twice daily significantly improved pulmonary resistance (2.7 ± 1.1 to 1.6 ± 0.8 cm H2 O/L/s), pulmonary elastance (5.2 ± 3.1 to 2.2 ± 1.3 cm H2 O/L), and weighted clinical score (13 ± 2.9 to 10.8 ± 4.2). Serum cortisol suppression (<50 nmol/L) systematically occurred with dexamethasone from day 3 of treatment up to day 3 post treatment, but not with ciclesonide at any tested doses. Placebo did not exert any significant beneficial effect. Main limitations: Experimentally induced asthma exacerbations in horses might respond differently to treatment than naturally occurring exacerbations. Conclusions: Inhaled ciclesonide is an effective treatment for horses with equine asthma. Serum cortisol was unaffected by treatment.